Narratives of Mothers Whose Children Had Been Sexually Abused: Maternal Reactions and Comprehension Regarding Child and Adolescent Sexual Abuse - Sufredini, Francieli (Journal of interpersonal violence, 2022)
Child and adolescent sexual abuse is considered to be a serious public health concern and a devastating form of violence with serious physical, mental, and behavioral consequences in the short and long term. This qualitative study aimed to identify maternal reactions to the disclosure of sexual violence and explore the comprehension regarding child and adolescent sexual abuse held by the mothers of child victims. Twelve mothers were interviewed, whose children had experienced a situation of sexual abuse and were receiving psychosocial care in a municipality in southern region of Brazil. The collected data were organized and analyzed using the principles of Grounded Theory with the Atlas.ti 7.5.7 software. From the analysis of the narratives, three main categories emerged: mothers with positive reactions, mothers with ambivalent reactions, and mothers with negative reactions. Mothers that presented positive reactions believed the report and supported their children, showing a comprehension that sexual abuse can occur in different ways and not only when there is penetration. The participants that had ambivalent reactions oscillated between maintaining or breaking off the relationship with the perpetrator of the violence, expressed initial disbelief regarding the report of the abused child, and had a comprehension that sexual abuse could be a form of affection. Mothers that had a negative reaction to the disclosure of abuse presented a contradictory narrative, minimizing the effects of the violence and placing the victims at fault regarding the abuse suffered. The importance of considering the possible relationships between the maternal comprehensions regarding child and adolescent sexual abuse and the reactions of these mothers during the professional intervention was demonstrated.